ANALISIS PULLEY PADA MESIN PENCACAH KALENG BERBANTUAN SOFTWARE SOLIDWORKS - Eko Susetyo Yulianto; Doddi Yuniardi; Achmad Risa Harfit; Candra Adi Setyawan (Asosiasi Dosen Muda Indonesia, 2024)
Waste is a material that is wasted or disposed of as a result of human activity or natural processes that does not yet have economic value. One way to help the process of crushing these bottles is to make a simple bottle crusher machine, it is hoped that this will increase work efficiency. Technological development is urgently needed to handle this for optimization, so a tool is made to help meet the needs of a can chopper, namely by designing a can chopper that will help the work to be faster and safer. This can chopper has dimensions of 1230 x 630 x 625 mm, with a power source generated by a 1 hp (0.746 kW) electric motor with 1400 rpm rotation and a gearbox. In designing the design of this cassava slicing machine using a pulley diameter of 56 mm and 124 mm which will be used to connect the rounds received from the motor. With a belt circumference of 680.49 mm, the actual shaft axis distance is 1161.2 mm and the contact angle between the belt and the pulley is around 169 with a ????????° correction factor of 0.97. Pulley simulation results using solidworks software with a torque load of 3.75 Nm on the pulley driver and 7.43 Nm on the driven pulley. From the provision of torque, the value of the von Mises stress on the pulley driver is 0.49 Mpa and the von Mises stress on the driven pulley is 12.68 MPa, the displacement value on the pulley driver is 0.000mm and the driven pulley is 0.0046mm, and the factor of safety value the safety on the pulley driver is 1070 ul and the safety factor on the pulley driver is 41.79 ul.